Occupational Exposure to Lead Fume Among Automobile Welders - Omolbanin Motamedrezaei; Hamed Lotfi; Farnaz Jahani; Gholam Reza Sharifzadeh; Farough Mohammadian; Fereydoon Laal (Epidemiology and Health System Journal)
Background and aims: Lead is one of the most dangerous toxic metals in the world. Therefore, this study aimed to investigate and assess the health risks of welders’ occupational exposure to lead fumes. Methods: A cross-sectional, descriptive-analytic study was conducted on 47 automobile welders. In this study, sampling and analysis of air lead concentration (ALC) were performed using the NIOSH 7082 standard and flame atomic absorption spectrophotometer. Then, the blood lead concentration (BLC) was measured using the NIOSH 8003 method via graphite furnace atomic absorption spectrophotometer. Additionally, the health risk assessment of people was conducted using the Environmental Protection Agency (EPA) method. Results: Among the workers, 12.8% were smokers, and 66% used appropriate personal protective equipment (PPE). The average ALC and BLC of automobile welders were equal to 0.0458±0.0296 mg/m3 and 9.89±7.32 μg/dL, respectively. Although the Pearson coefficient showed a positive correlation between ALCs and BLCs, this correlation was not statistically significant (P=0.38, r=0.18). The value of chronic daily intake (CDI) and lifetime cancer risk (LCR) for lead fume exposure was 74×10-5 and 31×10-6, respectively. Conclusion: This study found higher average BLC levels in smokers, those who did not use PPE and in individuals over 30 years of age compared to those under 30 years. The mean BLC and ALC were consistent with the American Conference of Governmental Industrial Hygienists (ACGIH) standards, and the carcinogenic risk of exposure to lead fume was within the possible risk range.